2016
DOI: 10.1128/mbio.00403-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Remodeling Contributes to Epidemic Disease Caused by the Human Pathogen Streptococcus pyogenes

Abstract: For over a century, a fundamental objective in infection biology research has been to understand the molecular processes contributing to the origin and perpetuation of epidemics. Divergent hypotheses have emerged concerning the extent to which environmental events or pathogen evolution dominates in these processes. Remarkably few studies bear on this important issue. Based on population pathogenomic analysis of 1,200 Streptococcus pyogenes type emm89 infection isolates, we report that a series of horizontal ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 83 publications
5
99
1
Order By: Relevance
“…According to our data, the clade 3 strain is T serotype 13 (corresponding to the tee89 gene) and associated with the decline of the T serotype 11 (corresponding to the tee11 gene) clade 1 emm89 strain (5) that expressed capsule and contained the less active nga promoter Pnga1. Although only two T11 (tee11) isolates (recovered in 1995 and 2000) and one T13 (tee89) isolate (recovered in 2000) were sequenced in this study prior to 2015, where all 185 isolates were sequenced, our data are entirely consistent with the previous reports and publicly available WGS data that include a large number (870) of these isolates recovered from 1995 to 2013 (4,5,36). Compare Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…According to our data, the clade 3 strain is T serotype 13 (corresponding to the tee89 gene) and associated with the decline of the T serotype 11 (corresponding to the tee11 gene) clade 1 emm89 strain (5) that expressed capsule and contained the less active nga promoter Pnga1. Although only two T11 (tee11) isolates (recovered in 1995 and 2000) and one T13 (tee89) isolate (recovered in 2000) were sequenced in this study prior to 2015, where all 185 isolates were sequenced, our data are entirely consistent with the previous reports and publicly available WGS data that include a large number (870) of these isolates recovered from 1995 to 2013 (4,5,36). Compare Fig.…”
Section: Resultssupporting
confidence: 82%
“…Recently, it was observed that infections due to emm AC cluster (or pattern A-C) strains peaked in the winter (first quarter, from January to March), while E cluster (4,5) associating the emergence of emm89 with the appearance of the acapsular clade 3 strain containing the upregulated nga operon promoter Pnga3 and a different tee gene (36). According to our data, the clade 3 strain is T serotype 13 (corresponding to the tee89 gene) and associated with the decline of the T serotype 11 (corresponding to the tee11 gene) clade 1 emm89 strain (5) that expressed capsule and contained the less active nga promoter Pnga1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in DNA sequencing and related technologies have facilitated genome-wide dissection of genetic events involved in colonization (6), immune evasion (7), virulence (8)(9)(10), and the evolution and spread of highly virulent S. pyogenes clones (11)(12)(13). To advance our understanding of S. pyogenes molecular-pathogenesis events occurring during invasive infection, we performed whole-genome sequencing of 2,954 isolates recovered from a nonhuman primate model of necrotizing fasciitis.…”
mentioning
confidence: 99%
“…Genetic changes in emm89 strains have recently generated clonal lineages responsible for invasive infections in different parts of the globe [12,13]. The high prevalence of noninvasive emm89 type strains in our collection confirmed the increasing expansion of this emm type together with its propensity to switch to more virulent variants, which is of concern and claims the continuous monitoring of its diffusion into the population [14].The analysis of the recorded patterns of virulence genes revealed the presence of major clones as already described in previous studies [4,15,16].…”
Section: Discussionmentioning
confidence: 99%